2015
DOI: 10.2340/00015555-2011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Satisfaction of Patients with Psoriasis

Abstract: Treatment satisfaction of patients with psoriasis largely depends on the treatment modality, but evidence on preferences for specific medications is scarce. Here we assessed treatment satisfaction of 200 participants with moderate-to-severe psoriasis from a German University hospital with a 5-point scale and the Treatment Satisfaction Questionnaire for Medication (TSQM) and determined sociodemographic and disease-related influence factors. Participants obtaining biologicals and traditional systemic medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
5
34
0
3
Order By: Relevance
“…Our patients seemed to regain good life quality, as documented by the low DLQI values throughout the treatment. Previous studies documented generally high satisfaction with biologic treatment in psoriasis [25], which could be confirmed in our cohort by the results of the MARS questionnaire sampling patients' beliefs and attitudes. In spite of the fact that low levels of nonadherence precluded conclusive analyses of correlation between psychologic factors and drug adherence, we observed that the patients with an MPR <0.8 had a lower TS on the MARS.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our patients seemed to regain good life quality, as documented by the low DLQI values throughout the treatment. Previous studies documented generally high satisfaction with biologic treatment in psoriasis [25], which could be confirmed in our cohort by the results of the MARS questionnaire sampling patients' beliefs and attitudes. In spite of the fact that low levels of nonadherence precluded conclusive analyses of correlation between psychologic factors and drug adherence, we observed that the patients with an MPR <0.8 had a lower TS on the MARS.…”
Section: Discussionsupporting
confidence: 68%
“…Messy and time-consuming topical treatments are less favored by patients compared to injectable agents or oral treatments [20,22,25]. Surprisingly, injectable drugs seem to be preferred over orally administered medicine [22], which helps in understanding the high adherence to biologics in our study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Many factors are involved, such as immunity, inflammation, cell proliferation, and apoptosis, and neurotransmitter and intracellular signal transduction pathways [5]. The immune factor-mediated inflammatory reaction can promote abnormal proliferation of KCs, ultimately leading to psoriasis; however, a satisfactory therapeutic effect on psoriasis can be achieved by inhibiting inflammation [6].…”
Section: Introductionmentioning
confidence: 99%
“…I parametri principali per determinare la soddisfazione dei pazienti per il trattamento sono l'efficacia e la via di somministrazione [19]. Uno studio recentemente condotto in Germania ha confermato che nella psoriasi moderata-severa i farmaci biotecnologici vengono preferiti ai farmaci sistemici tradizionali per l'elevata efficacia, il favorevole profilo rischio-beneficio e la comoda modalità di impiego [24]. Evidenze derivate da studi clinici interventistici e studi osservazionali hanno mostrato che il raggiungimento della condizione di clear skin è significativo sia in termini di definizione di gravità della malattia sia di QoL secondo la prospettiva del paziente.…”
Section: Controindicazioniunclassified